Measurements of Solar Radiation and Atmospheric Turbidity with Angstrom Pyrheliometers at Poona and Delhi during the I.G. Y. - MANI, ANNA; CHACKO, OOMMEN (MAUSAM, 1963)
A statistical study of frequency of depressions cyclones in the Bay of Bengal